Growth Performance, Carcass Characteristics and Meat Quality of Broiler Chicken in Response to Different Levels of Dietary Moringa Oleifera Leaf Meal - Sharma, Shashi; Poudel, Sabina; Pantha, Chiranjibi; Munakarmi, Reshmi; Shrestha, Riddhi; Poudel, Nabaraj; Paudyal, Narayan; Shrestha, Swoyam Prakash; Khanal, Doj Raj; Gurung, Yam Bahadur; Karki, Suman (Journal of the Institute of Agriculture and Animal Science, 2025)
This study investigated the effects of different levels of dietary Moringa oleifera leaf meal on growth performance, carcass characteristics and meat quality of broiler chicken. A total of 144 birds were allocated into four dietary treatment groups, each with three replications of 12 birds. The treatments were: a control diet with no Moringa oleifera (T1) and diets supplemented with 0.5% Moringa oleifera (T2); 1% (T3) and 1.5% (T4) Moringa oleifera leaf meal. The data were analyzed using one-way analysis of variance (ANOVA). The highest body weight was observed in T3 group (1% supplementation). While the yields of neck, wings, breast, back and overall dressing percentage showed no statistically significant differences (p>0.05) among treatments, thigh yield was significantly higher (p<0.05) in supplemented groups. Analysis of breast meat revealed significant differences (p<0.05) in moisture and fat content and protein percentage was not significantly affected (p>0.05). The dressing percentage and total offal were comparable between the 0.5 and 1% supplementation group. Similarly, the calcium and phosphorus content of breast meat were identical for 0.5 and 1% treatment. Therefore, it is recommended to add Moringa oleifera at 0.5 – 1% in broiler diets to improve performance, carcass quality and meat quality of broiler chicken.